Exploring the Degradation of Malachite Green Using Fenton and Photo-Fenton Processes - O, Egah G.; O, Obadimu C.; J, Ewenifa O.; K, Ndukwe B.; A, Adelagun R.O. (African Journal of Sciences and Traditional Medicine, 2024)
The degradation of Malachite green (MG) dye was studied using Fenton and Photo-Fenton processes. Batch experiment was conducted for the effect of pH at the range of (3–12), initial concentration at 50–250mg/L, effect of catalyst dosage of 0.2-1.0g, contact time (10–60min) and temperature (303–318) were eval_uated. For each experiment, the reactor was loaded with 30mL of 50mg/L of MG aqueous solution and 20ml of 50mmol of hydrogen peroxide to which 0.5g of the ferrous catalyst was added. As investigated, the degradation capacity of Fenton and Photo Fenton was favoured by an increase in dosage, concentration, and contact time. While degradation decreases with increase in temperature and pH. The optimum pH for the degradation of MG was found to be 3. The experimental data of MG fitted better into Freundlich equation indicating multilayer degradation. Also the Kinetic data fitted more into pseudo second order than in pseudo first order equation for both Fenton and photo Fenton suggesting chemisorptions as the rate limiting step. The negative value of enthalpy change (∆H), entropy change (∆S) and Gibbs free energy (∆G) indicating that the degradation of Malachite Green was exothermic and spontaneous, meaning that physisorption dominate chemisorptions. Overall, Fenton and Photo Fenton as investigated in the present study; it is an evident that Photo-Fenton has higher potency for degradation of Malachite green than that of Fenton.